European Union private international labour law / Andrzej Marian Swiatkowski. - Świątkowski, Andrzej (Jagiellonian University Press, 2012)
The European Union as an area of freedom, security and justice has created a community which adheres to unified laws. In matters regulated by labour law (individual and collective) as well as social security law, the above aim may be met by introducing unified regulations, allowing for identical ways of resolving conflicts of labour law that arise in work relations where there is a cross national element present. In order to ensure legal stability within work relations, national regulations concerning international private labour law had to be replaced by unified conflicts of law norms. These norms are to be applied by both employees and employers of EU member states as well as applied in work relations situations where third parties are involved. EU private international law is a collection of international private labour law regulations issued by EU institutions, which unanimously and in a unifying fashion describe the legal situations of the parties to a work relationship, where there is a foreign element present, allowing for the application of foreign laws based on citizenship, residency, where the headquarters of one of the parties is located, where the work is carried out or where the action has taken place.